Da'wah and Contemporary Muslim Women: A Historical Study of Sayyidah Khadijah - Malik, Rif'atul Khoiriah (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2024)
Sayyidah Khadijah's gait is part of the sacrifice and loyalty of a wife to her husband and supporter and encouragement of the Prophet's preaching, so that it can be felt the magnitude of the spread of Islam to date. Seeing the role of women that is so large, the writer chose to make the figure of Khadijah a Muslim figure today. Muslim women are now shackled by exploitative and entangled capitalist spheres in line with technological developments. Many of the Muslim women lost their figures, so many imitated Western or Korean Pop styles, for example. Today's Muslim women idolize and even imitate their lifestyle. Doesn't Islam have a figure that is no less fantastic? Even his name is known after centuries, he was Sayyidah Khadijah. This study uses a historical approach followed by an analysis of the role of Muslim women today, with the aim of reflecting back on the glory of Islam during the Prophet. Especially women as khairu ummah. Furthermore, to bring up the present Khadija, women should